Arang Aktif Kayu Leucaena Leucocephala sebagai Adsorben Minyak Goreng Bekas Pakai (Minyak Jelantah) - Hafidzi Nur Muhammad; Faizatun Nikmah; Nurul Umrotul Hidayah; Arghob Khofya Haqiqi (Physics Education Research Journal, 2020)
Cooking oil is a basic need for human life. Alternative processing of used cooking oil is through the adsorption process with leucaena leucocephala activated charcoal. This study aims to utilize leucaena leucocephala activated charcoal as an adsorbent of used cooking oil. Activated charcoal from leucaena leucocephala can reduce levels of free fatty acids and peroxide numbers of cooking oil before and after frying repeatedly so that used cooking oil can be reused. The method used in the study is the experimental method. Data collection was carried out by mixing leucaena leucocephala activated charcoal with used cooking oil. The composition of activated charcoal is 75%, while used cooking oil is 25% in one and a half hours. Research shows that activated charcoal can improve the quality of used cooking oil by lowering fatty acid levels, making the color of used cooking oil clearer. Leucaena leucocephala activated charcoal can be used as an alternative to oil adsorbent and research is needed for other types of oil.